Simulation of High-Visual Quality Scenes in Low-Cost Virtual Reality - Selzer, Matias Nicolas (2020)
With the increasing popularity of virtual reality, many video games and virtual experiences with high-visual quality have been developed recently. Virtual reality with a high-quality representationof scenes is still an experience linked to high-cost devices. There are currently low-cost virtual reality solutions by using mobile devices, but in those cases, the visual quality of the presented virtualenvironments must be simplified for running on mobile devices with limited hardware characteristics. In this work, we present a novel Image-Based Rendering technique for low-cost virtual reality. We haveconducted a performance evaluation of three mobile devices with different hardware characteristics. Results show that our technique represents high-visual quality virtual environments with considerablybetter performance compared to traditional rendering solutions.